An Antibiotic-Loaded Hydrogel Demonstrates Efficacy as Prophylaxis and Treatment in a Large Animal Model of Orthopaedic Device-Related Infection - Boot, Willemijn; Foster, Andrew Lewis; Guillaume, Olivier; Eglin, David; Schmid, Tanja; D’Este, Matteo; Zeiter, Stephan; Richards, Robert Geoff; Moriarty, Thomas Fintan (Frontiers in Cellular and Infection Microbiology, 2022)
Local antibiotic therapy is increasingly being recognised for its role in preventing and treating orthopaedic device-related infection (ODRI). A bioresorbable, injectable gentamicin-loaded hydrogel has been developed to deliver local antibiotics at the time of surgery with potential for both prevention and treatment of ODRI. In a prophylaxis model, the antibiotic hydrogel was compared with systemic perioperative antibiotic prophylaxis alone in twelve sheep (six per group) at the time of intramedullary (IM) nail insertion to the tibia, which was inoculated with methicillin-sensitive Staphylococcus aureus (MSSA). In a treatment model of single-stage revision surgery, adjunctive antibiotic-loaded hydrogel was compared with systemic antibiotics alone in a single stage revision of MSSA infection associated with a tibia intramedullary nail in eleven sheep (five/six per group). The primary endpoint was quantitative microbiological results of soft tissue, bone and sonicate fluid from explanted hardware at the time of euthanasia. At euthanasia, the control sheep that received no local antibiotics in the prophylaxis model were all culture-positive (median 1x108, range 7x106-3x108 colony forming units, CFU) while only two of six sheep receiving local gentamicin had any culture positive biopsies (median 1x101, range 0- 1x105 CFU). For the treatment model, sheep receiving only systemic antibiotics were all culture-positive (median 8x105, range 2x103- 9x106 CFU) while only two of six sheep treated with gentamicin-loaded hydrogel had any culture positive biopsies (median 3x102, range 0- 7x104 CFU). Local gentamicin concentrations measured in extracellular fluid in the tibial canal show a burst release of gentamicin from the hydrogel. Serum gentamicin concentrations peaked in both models at one day post application and were below detection limit thereafter. This study has demonstrated the effective use of a locally delivered antibiotic hydrogel for both the prevention and treatment of ODRI that is superior to that of systemic antibiotics alone. Future studies will endeavour to translate from preclinical to clinical research trials.